Additive manufacturing of silicon carbide by selective laser sintering of PA12 powders and polymer infiltration and pyrolysis. Issue 10 (August 2021) - Pelanconi, Marco; Colombo, Paolo; Ortona, Alberto
Graphical abstract: Abstract: In this work, we propose a novel hybrid additive manufacturing technique, which combines selective laser sintering (SLS) of polyamide powders and subsequent preceramic polymer infiltration and pyrolysis to manufacture Silicon Carbide components for complex architectures. By controlling the porosity of the sintered polymeric preform we are able to control the shrinkage upon the first infiltration and pyrolysis. This enabled the manufacturing of smaller features than those achievable with other manufacturing techniques. The mechanical strength of the resulting ceramic increased with the number of reinfiltration cycles up to 24 MPa, inversely the residual porosity decreased to 10 vol%. The microstructure showed two distinct phases of SiOC and SiC. The first was attributed to the interaction between the porous polyamide and the ceramic precursor during the first infiltration. SiC derived from the pyrolysis of the preceramic precursor alone.